Cold Vapour Generation and Atomic Fluorescence Spectrometry for the Determination of Mercury - LI, YINKE; XU, YIRANG; HUANG, YUN; DAI, YUN; HU, QIUFEN; YANG, GUANGYU (Asian Journal of Chemistry, 2010)
A new cold vapour generation and atomic fluorescence spectrometry method for the determination of mercury was developed by the simple addition of NaOH or other base to generate the mercury vapour at high pH. The samples were digested using HNO3 and H2O2 in a closed microwave vessel and the pH of the sample solution is increased to 13 by the addition of NaOH. After standing for 1.5 h in a closed vessel, the Hg0 was directly transfered into the atomic fluorescence spectrometry by a flow of argon. The conditions for the generation of volatile mercury species, the tolerance to the interference of coexisting ions were carefully examined. Under optimal conditions, the detection limits (3s) were evaluated to be 8.0 ng L-1 for mercury. This method was successfully applied to the determination of mercury in biological samples. The relative standard deviations are 3.3-3.6 %. The recoveries are 88-97 %.